Proceedings of the 13th Reinventing Space Conference (Springer International Publishing, 2018)
Reinventing Space is the largest global conference and exhibition for one of the space industry's fastest growing sectors. Over its 82-year history, the British Interplanetary Society has acted as a forum for new and innovative ideas and developments in astronautics, low-cost access and utilization of space. These conference proceedings reflect the work done at the 13th Reinventing Space Conference, the second biggest space event in the UK during 2015. The global economic climate is creating demand to reduce expenditure, leading to new challenges and opportunities in the world's space industry. The need to create more responsive systems and launchers that are capable of delivering to space quickly, cheaply and reliably has never been more vital. This collection from RIspace brings together industry, agency, government, financiers, academia and end users. It focuses on the commercialization of space and addresses a range of topics including low-cost launch opportunities, the rebirth of constellations, beyond LEO activities and novel technologies. These papers encourage and promote forward-thinking ideas and concepts for the future exploration and utilization of space. The proceedings address: • New ways of doing business in space - how do we make money on affordable and responsive space missions? • Tactical space systems - how do we best serve the needs of defense missions; civilian missions; the needs of emergency responders? • Interplanetary missions - can we use new technology to explore the Solar System at dramatically lower cost? • What are the methods, processes, and technologies that we can use to make major reductions in the cost of space missions? • New application areas for low-cost space systems - which ones can take advantage of newer, much lower-cost systems? • How do we educate and motivate the coming generation, without whom there won't be a space industry?